THE INFLUENCE OF THE TRAINING PROCESS ON INCREASING FUNCTIONAL CAPABILITIES OF PLAYERS (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the questions of physical loading ofplayers in football hall. The components of loading and their impact on functional abilities of students are studied.